Behavior of vascular resistance undergoing various pressure insufflation and perfusion on decellularized lungs. Issue 7 (3rd May 2016) - da Palma, Renata Kelly; Nonaka, Paula Naomi; Campillo, Noelia; Uriarte, Juan J.; Urbano, Jessica Julioti; Navajas, Daniel; Farré, Ramon; Oliveira, Luis V.F.
Abstract: Bioengineering of functional lung tissue by using whole lung scaffolds has been proposed as a potential alternative for patients awaiting lung transplant. Previous studies have demonstrated that vascular resistance (Rv) could be altered to optimize the process of obtaining suitable lung scaffolds. Therefore, this work was aimed at determining how lung inflation (tracheal pressure) and perfusion (pulmonary arterial pressure) affect vascular resistance. This study was carried out using the lungs excised from 5 healthy male Sprague-Dawley rats. The trachea was cannulated and connected to a continuous positive airway pressure (CPAP) device to provide a tracheal pressure ranging from 0 to 15 cmH2 O. The pulmonary artery was cannulated and connected to a controlled perfusion system with continuous pressure (gravimetric level) ranging from 5 to 30 cmH2 O. Effective Rv was calculated by ratio of pulmonary artery pressure ( P PA ) by pulmonary artery flow ( V ′PA ). Rv in the decellularized lungs scaffolds decreased at increasing V′ PA, stabilizing at a pulmonary arterial pressure greater than 20 cmH2 O. On the other hand, CPAP had no influence on vascular resistance in the lung scaffolds after being subjected to pulmonary artery pressure of 5 cmH2 O. In conclusion, compared to positive airway pressure, arterial lung pressure markedly influences the mechanics of vascular resistance in decellularized lungs.